Pengaruh Keterampilan Bahasa Guru terhadap Penalaran Siswa - Wahyuni Wahyuni (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2022)
Understanding the vocabulary that is part of the body of language contributes significantly to overall understanding in many areas of content, such as mathematical reasoning. Teachers are expected to be able to pay attention to the way children communicate their reasoning in order to respond appropriately to improve children's reasoning and communication in their mathematical thinking. This study explores specifically the effects on teachers' language skills in demonstration lessons while teaching mathematics in the classroom and the learning objectives of improving students' reasoning ability. The study involved teachers from three different schools in Langsa City. The large number of teachers does not seem to pay special attention in the course of demonstrations of the broader pattern of justification-based discourse being formed. Only with the introduction and understanding of these specific difficulties can teachers then begin to address the instructional needs of their students from a language perspective. Designing and delivering vocabulary instructions effectively is a necessary action. Failure to design, convey, and understand children's language will have an effect on the growth of their mathematical alignment. In an effort to improve the overall mathematical performance of students, teachers need to recognize the importance of language to children's mathematical reasoning.